Analysis of the transcriptome and metabolome reveals phenylpropanoid mechanism in common bean (Phaseolus vulgaris) responding to salt stress at sprout stage - Qi Zhang; Shukun Wang; Bin Qin; Hao‐yue Sun; Xian‐kai Yuan; Qi Wang; Junjie Xu; Zhengong Yin; Yan‐li Du; Ji‐dao Du; Caihua Li (Food and Energy Security, 2023)
Abstract Common bean (Phaseolus vulgaris) seeds are important legume crops and an important source of dietary proteins and carbohydrates. Therefore, it is important to develop strategies to improve salt tolerance in common beans. In this study, transcriptome and metabolome analyses were conducted on local common bean variety under salt stress at the sprout stage for a period of 0, 12, and 24 h. Results showed that phenylpropanoid pathways (including phenylpropanoid biosynthesis and phenylalanine metabolism) and flavonoid pathways (including flavonoid biosynthesis and flavone and flavonol biosynthesis) played an important role in controlling responses to salt stress as evidenced by analysis of differentially expression genes, common expression patterns, WCGNA, and differentially altered metabolites (DAMs) analyses. In addition, exploration of the activities of 4‐coumarate‐CoA ligase (4CL), caffeoyl‐CoA O‐methyltransferase (CCoAOMT), peroxidase (POD), chalcone isomerase (CHI), dihydroflavonol‐4‐reductase (DFR), and flavonol synthase (FLS) further showed that phenylpropanoid and flavonoid pathways participate in plant responses to salt stress. Moreover, the phenylpropanoid pathways and flavonoid pathways were found to be potential pathways regulating plant response to salt stress based on transcriptome and metabolome analysis. The activities of 4CL, CCoAOMT, POD, CHI, DFR, and FLS revealed that these pathways are crucial to the regulation of plant responses to salt stress. These findings provided theoretical basis for further improvement of salt tolerance in common bean.